Performance comparison of convolutional codes for UWB-WBAN applications - Sansoda, Buncha; Khattiya, Wannarit; Choomchuay, Somsak (My University, 2013)
A wireless body area network is a radio-frequency-based wireless networking technology that interconnects tiny nodes with sensor or actuator capabilities in, on, or around a human body. WBANs provide promising applications in medical monitoring systems to measure specified physiological data and also provide location-based information, if required. This paper we propose the preliminary investigation of the application of error control code to MAC layer data. Convolutional codes and punctured codes have been considered. The punctured codes are used to step up the code rate from its mother code rate. In our investigation, ECG data from MIT-BIH Arrhythmia databases are chosen as input data. The coding performance comparison is selected to various parameters such as constrain length and code rate. The result will be a compromise between errors correcting capability and needed to reduce the number of data bits in the channel. © 2013 IEEE.
Keywords: convolutional code; puctured; wirless body area network(WBAN)